The Correlation Between Accuracy Coding with Submission Status BPJS Health Inpatient Claim at UNS Surakarta Hospital - yeni tri utami; Aloysius Eka Wardaya; Yuli Prihatini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
BPJS Health claims are submission cost maintenance patient BPJS participants by the party House Sick to BPJS party that is carried out in a way collective and billed to BPJS every​ month . Application process claim payment health to BPJS Health not forever walk smooth and able pending claim occurs . Pending claim event can caused by several factor among them factor administration , factors coding , and factors medical research​ This will review in a way empirical Connection Accuracy Coding with Submission Status BPJS Kesehatan Inpatient Claims at UNS Surakarta Hospital. Research Methods Used is study observation analytic with cross-sectional approach . Population in the study This is all over file claim patient care BPJS Health hospitalization in January - October 2025 , namely as many as 9,091 files claim , whereas sample as many as 100 files were taken with method sample random Simple Random Sampling. Data analysis techniques in study use analysis univariate that is analysis descriptive that describes results of each variable . Research this also uses analysis bivariate with the Chi-Square statistical test using SPSS Version 25 which was used For test connection between two variables. The results of the chi-square test analysis obtained mark significant p = 0.000 (< 0.05) with mark Coefficient contingency 0.511. Then it can be concluded There is connection between accuracy coding to results submission claim care BPJS Kesehatan hospitalization at UNS Surakarta Hospital. Coefficient Value contingency 0.511 which means show connection between variables tightly